Audit Drawbacks: From Diagnosis to Prediction - Redko О. Yu. (Statistics of Ukraine, 2025)
The author explores the causes giving rise to a phenomenon of the recurrence, over the latest three years (2022–2024), of the drawbacks in audit entities’ practices regularly revealed by the external audit quality control. In spite of the continuous publicizing of annual reports by the Committee on Quality Control at the Audit Chamber of Ukraine, these drawbacks have been replicated by other audit entities. The author attempted to interpret this phenomenon of ignoring the cautions articulated by external auditors by other participants of the audit market in Ukraine. The main drawback of organizational nature is disregard for the requirements of both the current Ukrainian law and international standards of audit. It essentially means the omission of risks specific to the process of financial reporting. The author’s view is that the situation originates from within the domestic auditing community where the overwhelming majority of auditors burn out as professionals. This is an upshot of time-related factors and psychological pressures from perpetual and quick changes in the auditor’s profession. Besides that, while the overwhelming majority of auditors have reached the pension age, the auditors’ community has not been sufficiently replenished by youth. Today, Ukraine features a clear tendency towards the maximal centralization of regulation specific to audit, a policy pursued by the Ukrainian Ministry of Finance and its Audit Public Oversight Body of Ukraine. The forthcoming period will see the internal audit, its certification, and, maybe, even its licensing fully subordinated to the Ministry, a move virtually shutting down an opportunity for an influx of mature-age auditors in the internal audit. Far from all the existing internal auditors will have access to the certification, if they do not resort to corruptive steps. The existing auditors, therefore, will face the job-placement challenge. Also, the auditors will find themselves under the increasing pressure due to the implementation of innovative information technologies, artificial intelligence in particular. This requires the involvement of youth in the audit profession. But the old-generation auditors have gloomy prospects given the plummeting prestige of the auditor’s profession. The Ukrainian professional organizations of auditors not concerned with elaborating audit methodologies, and especially those not dealing with legal protection of practical auditors from the external quality control or with lobbying professional interests in legislative power bodies, will not likely to survive. At best, such organizations will turn into commercial training platforms or professional development hubs for both external and internal auditors. The author believes that it poses a threat of stagnation in the Ukrainian audit. But our auditors are used to it, especially ones who lived and worked in time of stagnation at the end of the Soviet era. So, we will continue to watch the events and do our job.